PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND TABLE DAPAT MENINGKATKAN HASIL BELAJAR PADA POKOK BAHASAN ARITMATIKA SOSIAL DI KELAS VII 8 SMP NEGERI 10 PEKANBARU: Application of Cooperative Learning Model of Round Table Type in Increasing the Results of Learning in the Subject of Social Aritmatics in Class VII 8 Negeri 10 Pekanbaru - Yulmaliza, Yulmaliza (Perspektif Pendidikan dan Keguruan, 2018)
Learning is essentially a process of interaction with all situations around individuals. Learning activities are the most basic activities in the whole process of education in schools. The success of educational attainment in schools depends on the learning process that students experience as students. Teachers as educators who are directly involved in the implementation of learning in charge of creating learning conditions that can make learners learn optimally to get a satisfactory learning outcomes.The learning process can be done in school, at home, or in the place of study guidance. For learning in school, learners are faced with a number of subjects, one of which is the subject of mathematics. Learning can be viewed as a process directed to the goals and processes of doing through various experiences. Learning is also a process of seeing, observing, and understanding things. Mathematics is one of the subjects received by students in junior high.Mathematics is a science that studies about the material, natural phenomena and mechanisms that occur therein. More simply can be said that math is closely related to daily life. What we experience, what we do, why it happens and why. Subjects in the subject of mathematics is not only a calculation, but also the ability of learners to understand the concept to link learning with daily life.One of the subjects of mathematics in the form of conceptual and calculation or theoretical understanding is social arithmetic. Based on the research results obtained the value of the first cycle, the second cycle daan third cycle in a row 81.85%, 84.50% and 87.43%.